Effects of anesthesia on cerebral oxygen saturation and prevention of brain injury during carotid endarterectomy - Aikebaier. Nuermaimaiti; Shan-shan Li; Yu-qian Li; Jian-rong Ye (Journal of Cardiothoracic Surgery)
Abstract Background This study aimed to investigate the effects of general intravenous anesthesia and combined inhalation anesthesia on regional saturation of oxygen (rSO2) and cerebral hemodynamics during carotid endarterectomy (CEA). Optimizing intraoperative brain protection strategies has become a key focus in CEA research. Methods Fifty-four patients (43 males, 11 females, aged 44–80) undergoing unilateral CEA were randomly assigned to Group IVA (intravenous anesthesia) or Group CIA (combined inhalation anesthesia), with 27 patients each. Group IVA was maintained with propofol and remifentanil, while Group CIA used sevoflurane, propofol, and remifentanil, with sevoflurane stopped after carotid exposure. Hemodynamics were controlled at various stages: ±10% before clamping, + 20% during clamping (metaraminol), and 0 to -10% after exposure. HR, MAP, and rSO₂ were recorded at T0 (pre-induction), T1 (pre-clamping), T2 (post-clamping), T3 (5 min post-clamping), T4 (10 min post-clamping), T5 (15 min post-clamping), and T6 (15 min post-reperfusion). Blood samples were taken at T1, T6, and T7 (24 h post-surgery) for blood gas and S100-β analysis. Results No significant differences in rSO₂ were observed at T0 and T6 (P > 0.05). However, Group CIA had significantly higher rScO₂ at T1, T2, T3, T4, and T5 (P < 0.05). From T2 to T5, rSO₂ increased in both groups (P < 0.05). MAP and HR showed no significant differences (P > 0.05). ΔrSO₂ increased more in Group CIA (P < 0.05). At T6, S100-β protein was higher in Group IVA (P = 0.016), and pH differed significantly at T1 (P = 0.009). No other significant differences were observed. Conclusion Both intravenous and combined inhalation anesthesia may reduce rSO₂ decline during temporary clamping in CEA. Combined inhalation anesthesia showed a trend toward higher rSO₂ levels, potentially leading to better outcomes, but further studies are needed to confirm these findings. Retrospectively registered clinical trial number ISRCTN17014575; Registration Date: 2024/6/10.